CP-059 Efficacy and cost of direct acting antivirals for the treatment of hcv infection among HCV monoinfected and HIV/HCV coinfected patients in real life setting. (25th February 2017) - Corinaldesi, G; Sentinelli, R; Guglielmi, S; Barocci, V; Castelletti, S; Pierantonelli, I; Gemini, S; Riva, A; Martini, M; Costantini, A
Abstract : This abstract was published in error and withdrawn at the author's request.